Phương pháp hòa tách thu hồi triệt để niken trong bã thải công nghiệp mạ điện niken - Thắng, Phạm Đức; Khoa, Ngô Huy; Duyên, Đỗ Thị; Hải, Nguyễn Phúc; Kim Chi, Nguyễn Thị (Vietnam Journal of Chemistry, 2014)
The article describes the nickel recovery process by using dissolving method in order to dissolve alternately the hydroxide typed indissoluble ones from Nickel contained galvanization waste. The ICP-MS results show that, after some dissolving steps at room temperature the last one with boiling temperature at 100oC permits to recovery almost whole of nickel quantity. In this case the nickel recovery rate can reach up to 98.61%. Thus for better recovery efficiency the process should be rather conducted at 100oC than at room temperature.